The Impact of Family Functioning on College Students’ Loneliness: Chain-Mediating Effects of Core Self-Evaluation and Problematic Mobile Phone Use - Qian, Ling; Wang, Die; Jiang, Min; Wu, Wei; Ni, Congying (Frontiers in Psychology, 2022)
Purpose: To examine the influence of family functioning on college students' loneliness and the mediating effects of core self-evaluation and problematic mobile phone use. Methods: Family Function Scale, Core Self-evaluation Scale, Problem Mobile Phone Use Scale and Loneliness Scale were used to investigate 8524 college students. Results: (1) Family functioning positively predicted core self-evaluation and negatively predicted loneliness; (2) Core self-evaluation negatively predicted problematic mobile phone use and loneliness; (3) Problematic mobile phone use significantly positively predicted loneliness; (4) Core self-evaluation and problematic mobile phone use showed a significant chain-mediation effect between family functioning and loneliness. Conclusion: The results are helpful to comprehend the producing mechanism of loneliness and provide a theoretical basis for the intervention of loneliness.